A study of the effects of preservative solutions on the dielectric properties of biological tissue. Issue 3 (14th December 2017) - Bonello, Julian; Farrugia, Lourdes; Schembri Wismayer, Pierre; Alborova, Irina L.; Sammut, Charles V.
Abstract: Dielectric properties of biological tissue are important in view of emerging medical applications. We report on dielectric properties of ex vivo porcine fat and muscle and the effect of 10% formalin and Thiel Embalming solution (TES) as preservatives on the dielectric properties. This study is important as understanding the effect of such preservative solutions would allow for measurements to be done even days after excision. In this study, dielectric measurements were conducted on fat and muscle samples before and after preservation. Measurements were conducted between 0.5 and 20 GHz. All results obtained were fitted to a Debye model and uncertainty limits analyzed carefully. We also present the percentage difference in dielectric properties of fresh tissue and preserved tissue. The results show that changes in the dielectric properties due to tissue preservation depend on the type of tissue studied, the technique used and the test frequency. In fact, an increase in the real part of permittivity ϵ ′ of fat was observed compared with a decrease in that measured for muscle, when both preserved in TES. Moreover, the imaginary part of permittivity ϵ ″ of muscle preserved in TES increases at low frequency but then decreases at frequencies higher than 10.8 GHz. The changes in the dielectric properties of fat and muscle when preserved in 10% formalin reach a constant value above 5 GHz.